Brain health throughout cancer survivorship: the impacts of anti-cancer therapy on cerebrovascular regulation and pathology - Scheuermann, Britton Charles (My University, 2025)
Cancer survivors have substantially greater risk of cardiovascular morbidity and mortality compared to the general population, including a 52% greater risk of heart failure and a 22% greater risk of stroke in some reports. The rates of development of chronic disease, even without immediately fatal endpoints, are similarly worrisome. Addressing both “hard” cardiovascular disease events and the incident development or exacerbation of chronic disease remains critical in the care of cancer survivors. This is even more true today with the increasingly rapid pace of progress in oncology – specifically, the introduction of immune checkpoint inhibitors. One of the primary concerns addressed in the present dissertation is neurotoxicity, experienced by many cancer survivors as a consequence of both the burden of cancer and due to adverse off-target effects of anti-cancer treatment. This neurotoxicity can manifest in a variety of ways, including cognitive decline, cerebral pathologies like encephalitis or reversible cerebral vasoconstriction syndrome, or in severe cases, stroke or intracranial hemorrhage. Despite the serious and harmful nature of these toxicities, investigations into overall brain health in cancer survivors are limited compared to the research dedicated to other organ systems. Therefore, in this dissertation, we present a series of four studies aimed at investigating cerebral and cerebrovascular health in cancer survivorship. Our first investigation was a systematic review and meta-analysis examining the associations between two local cerebrovascular regulatory functions (cerebrovascular reactivity, cerebral autoregulation) and one systemic vascular characteristic (arterial stiffness) with cerebral small vessel disease. Subsequently, we aimed to determine if there were impairments in cerebrovascular reactivity in cancer survivors compared to cancer-free controls. We then combined evidence from the first two studies to form a base of evidence suggesting that cancer survivors were likely to be at risk for cerebral small vessel disease. This led to our last two studies focused on a novel class of anti-cancer treatment, called immune checkpoint inhibitors (ICI). Our third study uses Mendelian randomization and human genetic information to explore relationships between exposure to ICI treatment and the risk of developing cerebral small vessel disease. Finally, our fourth study expands on the previous study’s findings with single-cell RNA-sequencing of vascular tissue from patients who did or did not receive ICI treatment. This patient tissue-derived information is combined with genomic and epigenetic analyses to investigate biological processes and pathways linking ICI exposure to cerebral small vessel disease, and to subsequently identify possible therapeutic options. It is our hope that this dissertation may provide insight into the cerebrovascular complications that exist in cancer survivorship, as well as their potential causes and consequences.
Keywords: Cardio-oncology; Chemotherapy; Immune checkpoints; Cerebrovascular; Cognitive function; Cancer survivorship